Full- and pilot-scale GAC adsorption of organic micropollutants. (1st January 2015) - Kennedy, Anthony M.; Reinert, Allison M.; Knappe, Detlef R.U.; Ferrer, Imma; Summers, R.Scott
Abstract: Granular activated carbon (GAC) adsorption of 30 environmentally relevant micropollutants (MP) from four surface waters was investigated at the pilot-scale with empty bed contact times (EBCTs) of 7 and 15 min. An increase in background dissolved organic matter resulted in more and earlier MP breakthrough. Compared to an EBCT of 7 min, MP breakthrough at an EBCT of 15 min demonstrated 52% later breakthrough on average for five MPs on a throughput basis. A regression model was developed with data from three waters to predict MP throughput in bed volumes to 10% breakthrough (BV10% ) based on the influent dissolved organic carbon concentration and the MP pH-dependent octanol–water partition coefficient, polarizability, and molecular volume. The regression model over predicted full-scale BV10% values when applied to a wastewater-water impacted water source and to GAC with a larger particle diameter, for which a particle size adjustment was able to account for most of the difference. Graphical abstract: Highlights: The 30 organic micropollutants studied broke though after DOC did in all five waters. For the three runs with coagulated DOM and the same GAC, higher DOC0 caused earlier MP breakthrough. A relationship for BV10% was developed with DOC0, MP log D, MP polarizability, and MP molecular volume. Observed BV10% values in an anthropogenic impacted water were lower than predicted.